The Polowijen Cultural Village Sector of Halal Destinations as A Medium for Regional Economic Resilience Post Covid-19 Pandemic - Yudha, Ana Toni Roby Candra; Febriyanti, Novi; Rofiqoh, Isnaini (Ecoplan, 2023)
This research aims to determine the potential and opportunities of the area as well as the readiness of the Polowijen Cultural Village sector to become a halal tourism area and provide a strategic evaluation. This research uses a descriptive qualitative approach. Primary data sources and some secondary data as research data sources dominate this research. The data analysis techniques used by researchers in formulating strategies is the strategic environmental analysis and SWOT analysis. The results of the research show that the current readiness of the Polowijen Cultural Village Tourism sector is inadequate for Islamic tourism. The lack of public facilities and supporting facilities for tourists is the most important factor in implementing Sharia tourism. Further research results show that Polowijen Cultural Village tourism is in quadrant III (Turn Around). Suggestions that are relevant to these results are that the Malang village and district governments need to work together by publishing via social media, issuing special regulations from the village, sub-district to central levels regarding investment, and developing educational and literacy aspects about halal tourism. Suggestions that are relevant to these results are that the Malang village and district governments need to work together by publishing via social media, issuing special regulations from the village, sub-district to central levels regarding investment, and developing educational and literacy aspects about halal tourism.